Exploration of Traditional and Modern Values of Bidara (Ziziphus mauritiana) Leaf in the Community of Tancung Village, Tanah Sitolo Sub-District, Wajo District - nurhaeda, zahra (Hayyan Journal, 2025)
This study aims to explore the utilization and meaning of bidara leaves (Ziziphus mauritiana) in the lives of people from various generational and professional backgrounds. Data were obtained through interviews with six resource persons, namely traditional healers, housewives, fathers, grandmothers, millennial aunts, and local residents. The results of the interviews showed that bidara leaves have strong traditional values, such as being used in the ritual of bathing corpses, treating wounds, and treating supernatural disorders. On the other hand, modern uses are starting to develop, such as being used in beauty products, skincare, and as a symbol of spiritual healing on social media. The findings show that bidara leaves have not only survived as part of tradition, but have also been successfully adapted into modern lifestyles, reflecting the continuity and transformation of values in society.